2000
DOI: 10.1002/1098-2795(200007)56:3<372::aid-mrd7>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Electrofusion of two-cell bovine embryos for the production of tetraploid blastocysts in vitro

Abstract: Tetraploid bovine blastocysts were produced experimentally by electrofusion of in vitro matured and fertilized, zona‐enclosed two‐cell embryos (33–35 hr after initiation of sperm–egg incubation) using three fusion protocols. Field strengths of 1.0, 1.4, and 2.4 kV/cm were tested and the rate of fusion, subsequent cleavage, and blastocyst development were measured for each. High rates of fusion (76.5% ± 2.8%), cleavage (72.5% ± 7.4%) and blastocyst development (56.1% ± 6.4%) were achieved with the application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 26 publications
1
9
1
Order By: Relevance
“…Aneuploidy was increased in 4-to 8-cell stage embryos subjected to the electrical pulse that did not fuse, even though blastocyst development was not affected. Additionally, in accordance with our results, it has been reported in cattle that aneuploidy is a result of asynchronous cleavage between two-cell embryos and asynchronous nuclear status of blastomeres within the embryo suggesting that blastomeres need to be at a certain stage of the cell cycle for consistent production of tetraploids (Curnow et al 2000). In agreement with our results, previous reports showed that higher electric pulse voltage affects efficiency of electrofusion and embryo survival (Meghji & Burnstock 1995, Suo et al 2009, Razza et al 2016.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Aneuploidy was increased in 4-to 8-cell stage embryos subjected to the electrical pulse that did not fuse, even though blastocyst development was not affected. Additionally, in accordance with our results, it has been reported in cattle that aneuploidy is a result of asynchronous cleavage between two-cell embryos and asynchronous nuclear status of blastomeres within the embryo suggesting that blastomeres need to be at a certain stage of the cell cycle for consistent production of tetraploids (Curnow et al 2000). In agreement with our results, previous reports showed that higher electric pulse voltage affects efficiency of electrofusion and embryo survival (Meghji & Burnstock 1995, Suo et al 2009, Razza et al 2016.…”
Section: Discussionsupporting
confidence: 93%
“…Tetraploid (4n-cells) complementation contributes to extra-embryonic tissue and reduces maternalfetal failures during implantation and placentation by improving placenta compatibility (Lin et al 2011, Curnow et al 2000. Tetraploid complementation has been used to study pluripotency and developmental capacity in mice by injecting stem cells or induced pluripotent stem cells (iPS cells) into a tetraploid blastocyst.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, two diploid blastomeres can be fused using polyethylene glycol (Eglitis, 1980; Spindle, 1981), inactivated Sendai virus (O'Neill et al ., 1990) or electrofusion (Berg, 1982; Kubiak & Tarkowski, 1985). Stimulation of 2-cell embryo fusion by electrical pulses appears to be the most efficient method and has been used to produce tetraploid embryos in a number of species including mouse (Kubiak & Tarkowski, 1985), rabbit (Ozil & Modlinski, 1986), cow (Iwasaki et al ., 1989; Curnow et al ., 2000), pig (Prather et al ., 1996; Prochazka et al ., 2004) and rat (Krivokharchenko et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, no hexaploid mammal was known. Electrofusion of blastomeres at the 2-cell stage was indicated as an effective method to produce tetraploid embryos in mammals (Kubiak et al ., 1985; Prather et al ., 1996; Curnow et al ., 2000; Krivokharchenko et al ., 2002). In the mouse, the aggregation of nuclear transfer embryonic stem cells (nt-ESC) with tetraploid embryos has allowed the birth of cloned offspring completely derived from those terminal differentiated cells like lymphatic or olfactory neurons (Hochedlinger et al ., 2002; Li et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%